Climate change and the far right. (15th August 2019) - Forchtner, Bernhard
Abstract: In recent years two crises have populated the imagination of publics: environmental crises, ranging from, for example, water and air pollution to climate change, and the crisis of liberal democracy, illustrated by the rise of far‐right actors across Europe, the United States and beyond. While these environmental and political crises have been analyzed on their own, little research has been done on their nexus. Against this background, this focus article reviews existing academic literature on far‐right climate‐change communication by European party and nonparty actors, that is, climate‐change communication from a distinctively ethno‐nationalist and authoritarian perspective. The far right is not a homogenous entity but best viewed as a continuum, ranging from radical‐right, anti‐liberal democracy actors to extreme‐right, anti‐democracy ones. This contribution to WIREs Climate Change argues that many, though not all, far‐right party and nonparty actors are skeptical towards (anthropogenic) climate change and/or responses to it, at least in comparison to the European mainstream. The article does so by reviewing existing research before formulating areas for further research. This article is categorized under: Social Status of Climate Change Knowledge > Climate Science and Social Movements